Insurance, railways and the press: the 1864 fires at the MZA facilities in Madrid - González Jurado, Deborah (Cuadernos de Historia Contemporánea, 2018)
In this work we broach the conection between the press, the secure companies and the railways in Spain in the middle of XIX century, with an starting point on a concrete event as a revealing element. We will base on two types of principal sources: the Consell Acts of Administration, Railways Company from Madrid to Zaragoza and Alicante (MZA) and the press of that period.
Keywords: railways; insurance; press; companies; fires; advertising; nineteenth century.